Association of intracranial pressure with outcome in comatose patients with intracerebral hemorrhage - Sykora, Marek; Poli, Sven (Journal of the neurological sciences, 2014)
Background - Therapeutic targets for intracranial pressure (ICP) in patients with severe intracerebral hemorrhage (ICH) are approximated from data of traumatic brain injury. However, specific data for ICH are lacking. Here, we aimed to investigate the association between ICP, mortality and functional outcome following severe ICH. - Methods - We analyzed consecutive comatose patients with ICH in whom ICP monitoring was applied. Outcome at 3months was assessed using the modified Rankin scale (mRS). Multivariate logistic regression including pre-defined predictors was used in order to identify the effects of ICP on outcome. - Results - 121 patients with ICH and ICP monitoring were analyzed. Mean ICP (OR 1.2, CI 1.08-1.45, p=0.003), ICP variability (OR 1.3, CI 1.03-1.73, p=0.03) and relative frequency of ICP values >20mmHg (OR 1.1, CI 1.02- 1.15, p=0.008) were independently associated with mortality at 3months. Relative frequency of ICP values >20mmHg (OR 1.1, CI 1.001-1.3, p=0.04) was associated also with poor functional outcome at 3months. - Conclusions - Our data suggest that in the context of other predictors as age, admission clinical status, hemorrhage volume and intraventricular hemorrhage, average ICP, ICP variability and the frequency of ICP values >20mmHg are independently associated with mortality and poor outcome after ICH. Further studies and prospective validations of ICP thresholds for ICH patients are highly warranted.
Gesehen am 05.08.2020